2022
DOI: 10.21203/rs.3.rs-2240225/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of dog breed diversity using a composite selection index.

Abstract: During breed development, domestic dogs have undergone genetic bottlenecks and sustained selective pressures, as a result distinctive genomic diversity occurs to varying degrees within and between breed groups. This diversity can be identified using standard methods or combinations of these methods. This study explored the application of a combined selection index, composite selection signals (CSS), derived from multiple methods to an existing genotype dataset from three breed groups developed in distinct regi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Indeed, it is likely that multiple relevant associations are not detected by GWAS using SNP genotyping and common undetected variants within a breed or clade may contribute to the phenotype. In the Bullmastiff dogs in this study and in previous studies [ 69 , 70 ], we identified genomic signatures that have the potential to contribute to disease risk; for example, a well-known region on CFA26 that is commonly found in mastiff breeds contains candidate genes that have been implicated in cancer risk [ 71 ]. Many of these regions have complex functional annotations, and unravelling their role in disease may benefit from current efforts towards large-scale sequence analysis of the canine genome and eventual detailed functional validation [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, it is likely that multiple relevant associations are not detected by GWAS using SNP genotyping and common undetected variants within a breed or clade may contribute to the phenotype. In the Bullmastiff dogs in this study and in previous studies [ 69 , 70 ], we identified genomic signatures that have the potential to contribute to disease risk; for example, a well-known region on CFA26 that is commonly found in mastiff breeds contains candidate genes that have been implicated in cancer risk [ 71 ]. Many of these regions have complex functional annotations, and unravelling their role in disease may benefit from current efforts towards large-scale sequence analysis of the canine genome and eventual detailed functional validation [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 97%